Study on clinical symptoms and diagnosis in cases of vagal indigestion in cattle (Journal of Hama University, 2019)
Vagal indigestion (Hoflund's syndrome) is a syndrome characterized by impaired emptying of the forestomach, the abomasum, or both and gradual development of abdominal distention which is caused by total or partial damage of N. Vagus which stimulate rumen, reticulum, omasum and abomasum. This study is conducted on /12/ cows of different breeds, their ages ranging between           /3-8/years, six cows clinically diagnosed with vagal indigestion (Hoflund's syndrome) served as experimental group, and six cows served as the control group. The animals of experimental group have partial or complete anorexia, reduced water intake, scanty faecal output, and mild to moderate dehydration, bilateral abdominal distension and shaped abdomen ''papple'' (pear-apple). Heart and respiration rates are  reduced and rumen motility is more than the control group in some cases and less in another case. The laboratory results of the blood analysis show an increase in the number of red blood cells and white blood cells, and the height of Haematocrit, and the Neutrophil counts are higher than the control values, and the lymphocyte counts are lower than the control, increased concentration of total protein. Chloride ratio, sodium and  potassium are lower than the control values. Phosphorus ratio and magnesium do not differ significantly from the control values . In this review, It is given information about classification of vagal indigestion, etiology,  clinical findings, diagnosis and differential diagnosis, and prognosis vagal indigestion.